Non-invasive assessment of respiratory muscle function and its relationship to exercise tolerance in patients with chronic obstructive pulmonary disease - Chlumský, J; Filipova, P; Terl, M (The Journal of international medical research, 2006)
Most patients with chronic obstructive pulmonary disease (COPD) have impaired respiratory muscle function. Maximal oesophageal pressure correlates closely with exercise tolerance and seems to predict the distance walked during the 6-min walk test. This study assessed the non-invasive parameters of respiratory muscle function in 41 patients with COPD to investigate their relationship to pulmonary function tests and exercise tolerance. The COPD patients, who demonstrated the full range of airway obstruction severity, had a mean forced expiratory volume in 1 s of 42.5% predicted (range, 20 - 79% predicted). Both the maximal inspiratory muscle strength and non-invasive tension-time index were significantly correlated with the degree of lung hyperinflation, as expressed by the ratio of residual volume to total lung capacity, and the distance walked in 6 min. We conclude that respiratory muscle function was influenced mainly by lung hyperinflation and that it had an important effect on exercise tolerance in COPD patients.
Keywords: Statistics as Topic; Exercise Tolerance; Female; statistika jako téma; ženské pohlaví; lidé; Pulmonary Disease, Chronic Obstructive; Aged, 80 and over; chronická obstrukční plicní nemoc; Male; Aged; Respiratory Muscles; tolerance zátěže; lidé středního věku; Respiratory Function Tests; senioři nad 80 let; senioři; mužské pohlaví; respirační funkční testy; dýchací svaly; Middle Aged; Humans